Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.4093/dmj.2011.35.1.58
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion and Incretin Hormone Concentration in Women with Previous Gestational Diabetes Mellitus

Abstract: BackgroundWe examined the change in the levels of incretin hormone and effects of glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide 1 (GLP-1) on insulin secretion in women with previous gestational diabetes (pGDM).MethodsA 75-g oral glucose tolerance test (OGTT) was conducted on 34 women with pGDM. In addition, 11 women with normal glucose tolerance, matched for age, height and weight, were also tested. The insulin, GIP, GLP-1, and glucagon concentrations were measured, and their ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…The elevated postprandial GIP responses observed in the patients with GDM volunteering in the present study (during TT as well as during PP), is consistent with previous findings of higher GIP levels in women with previous GDM [33], and could represent an early consequence of disturbed glucose homeostasis. Thus, increased postprandial response of GIP (by some perceived as a 'diabetogenic' hormone -perhaps acting via glucagonotropic signalling [9][10][11]) could, perhaps, contribute to the increased susceptibility to development of type 2 diabetes among GDM patients.…”
Section: Original Articlesupporting
confidence: 93%
“…The elevated postprandial GIP responses observed in the patients with GDM volunteering in the present study (during TT as well as during PP), is consistent with previous findings of higher GIP levels in women with previous GDM [33], and could represent an early consequence of disturbed glucose homeostasis. Thus, increased postprandial response of GIP (by some perceived as a 'diabetogenic' hormone -perhaps acting via glucagonotropic signalling [9][10][11]) could, perhaps, contribute to the increased susceptibility to development of type 2 diabetes among GDM patients.…”
Section: Original Articlesupporting
confidence: 93%
“…In line with our findings, decreased GLP-1 secretion during OGTT and lower second-phase GLP-1/glucose ratios were observed in post-GDM normoglycemic women9 and in post-GDM women who had developed pre-diabetes 15. In a smaller study, a preserved GLP-1 response to oral glucose was described in normoglycemic women after GDM 13. These discrepancies may be explained by differences in the phenotype of study participants, for example, the degree of obesity and insulin resistance, the average time after the index pregnancy (2–3 months to several years), and the assays used to measure total or intact GLP-1 plasma concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Controversial results were also reported postpartum. A slightly reduced GLP-1 response to oral glucose load was observed in normoglycemic post-GDM women,9 12 whereas other studies showed no difference13 14 or detected decreased GLP-1 secretion in post-GDM women having developed a pre-diabetic metabolic state 15…”
Section: Introductionmentioning
confidence: 99%
“… 1 2 GDM can cause various perinatal and fetal complications, such as preeclampsia, macrosomia, and fetal distress, and affects the short- or long-term risk of type 2 diabetes and cardiovascular disease of the mother even after delivery. 2 3 4 5 In normal pregnancy conditions, insulin resistance increases according to fetal growth, and the beta cells of the pancreas promote cell proliferation and secrete more insulin in response to the insulin requirement. GDM is characterized by the inability of pancreatic beta cells to respond adequately to increased insulin resistance, resulting in hyperglycemia of various degrees.…”
Section: Introductionmentioning
confidence: 99%